The role of Malaysian palm oil industry in the Malaysian sustainable economic development - Mohammed Ebrahim Hussein; Chamhuri Siwar; Khairul Naim Adham (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2017)
In traditional business philosophy, companies are largely motivated by three determinants in order to maintain their competitiveness: product quality, cost and product delivery. The efficiency dimension of the company is determined by producing a product maintaining its quality, with less cost and distributing it using efficient delivery system. Regardless of social and environmental issues, companies were used to focus on financial and economic aspects of the business in order to determine the growth of their profitability and market share. However, in the last few decades, especially as of the United Nations Conference on Environment and Development (UNCED) or the Earth Summit in 1992, business companies began to incorporate environmental issues as one of determinant factors for their profitability and market share. This study assesses the role of Malaysian palm oil industry in the Malaysian sustainable economic development. Utilizing secondary data, the paper uses the concept of national income accounting approach to show the contribution of Malaysian palm oil industry in the aggregate economy. The study shows that the Malaysian palm oil industry is playing a significant role in sustaining Malaysian economic development via high production and cleaner environment. Keywords: Green economy; sustainable development; sustainable oil palm; palm oil industry